2019
DOI: 10.1111/ecc.13045
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity self‐efficacy mediates the effect of symptom distress on exercise involvement among adolescents undergoing cancer treatment

Abstract: The objective of this study was to examine whether physical activity self‐efficacy mediated the adverse effect of symptom distress on exercise involvement among adolescents undergoing cancer treatment. A secondary data analysis approach was used to analyse a pooled sample of 97 adolescents who were undergoing cancer treatment in paediatric oncology/haematology wards and ambulatory settings in northern Taiwan. Mediation analysis was performed to examine the mediation relationship among physical activity self‐ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…There is a significant relationship between social support and physical activity participation 53 . A mediating effect of physical activity self‐efficacy on the relationship between symptom distress and exercise participation in AYACPs who are undergoing cancer treatment 54 . Previous studies mostly showed the maintenance effect of physical activity program 2 months after the intervention 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant relationship between social support and physical activity participation 53 . A mediating effect of physical activity self‐efficacy on the relationship between symptom distress and exercise participation in AYACPs who are undergoing cancer treatment 54 . Previous studies mostly showed the maintenance effect of physical activity program 2 months after the intervention 55 .…”
Section: Discussionmentioning
confidence: 99%
“… 53 A mediating effect of physical activity self‐efficacy on the relationship between symptom distress and exercise participation in AYACPs who are undergoing cancer treatment. 54 Previous studies mostly showed the maintenance effect of physical activity program 2 months after the intervention. 55 Despite the small difference in the extension time, it still provides a realistic basis for the long‐term maintenance of the exercise program intervention effect.…”
Section: Discussionmentioning
confidence: 99%
“…O estudo 29 evidenciou mais dados sobre pacientes com leucemia. Contudo, o mesmo abordando outros cânceres, em conjunto como o linfoma não-Hodgkin, osteossarcoma e tumores cerebrais em adolescente entre 13 e 20 anos.…”
Section: Discussionunclassified
“…Access to rehabilitation services, assistance in resuming progress on achieving life skills, and psychosocial support are all vital parts of effective follow‐up to restoring quality of life for AYA patients 94 . Screening to identify rehabilitation needs and physical rehabilitation with exercise and physical activity prescription improves physical sequelae of therapy, with a resultant positive impact on well‐being and quality of life 95–97 . The psychological, social, and physical needs of AYA sarcoma survivors require a personalized approach and holistic guidance and care from a proactive multidisciplinary team that understands psychological adaptation and recovery as dynamic systems 98 …”
Section: Areas Of Clinical Uncertainty For Ayasmentioning
confidence: 99%